QoS in Wireless Mesh Networks- A Review - Sandhu, Preet Pavneet Kaur; Saini, Prof. Jatinder Singh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This paper is a review on QoS issue of Wireless mesh networks. QoS comes up with a great collection of networking technologies and procedures that guarantees the capability of a network to deliver with predictable consequences. WMNs have emerged as a flexible, reliable and cost effective way of providing broadband internet access over wide areas through multi hop communication. This paper has reviewed different routing protocols usedÂ in the WMNs. The overall objective of this paper is to explore the various short comings of the routing protocols of WMN.